Ravenna : capital of empire, crucible of Europe - Herrin, Judith (Princeton : Princeton University Press, 2020)
At the end of the fourth century, as the power of Rome faded and Constantinople became the seat of empire, a new capital city was rising in the West. Here, in Ravenna on the coast of Italy, Arian Goths and Catholic Romans competed to produce an unrivaled concentration of buildings and astonishing mosaics. For three centuries, the city attracted scholars, lawyers, craftsmen, and religious luminaries, becoming a true cultural and political capital. Bringing this extraordinary history marvelously to life, Judith Herrin rewrites the history of East and West in the Mediterranean world before the rise of Islam and shows how, thanks to Byzantine influence, Ravenna played a crucial role in the development of medieval Christendom. Drawing on deep, original research, Herrin tells the personal stories of Ravenna while setting them in a sweeping synthesis of Mediterranean and Christian history. She narrates the lives of the Empress Galla Placidia and the Gothic king Theoderic and describes the achievements of an amazing cosmographer and a doctor who revived Greek medical knowledge in Italy, demolishing the idea that the West just descended into the medieval "Dark Ages." Beautifully illustrated and drawing on the latest archaeological findings, this monumental book provides a bold new interpretation of Ravenna's lasting influence on the culture of Europe and the West.
The emergence of Ravenna as the imperial capital of the West -- Part One 390-450. Galla Palacidia. Galla Placidia, Theodosian princess -- Honorius (395-423) and the development of Ravenna -- Galla Placidia at the western court (416-23) -- Galla Placidia, builder and empress mother -- Part Two 450-93. The rise of the bishops. Valentinian III and Bishop Neon -- Sidonius Apollinaris in Ravenna -- Romulus Augustulus and King Odoacer -- Part Three 493-540. Theoderic the Goth, Arian King of Ravenna. Theoderic the Ostrogoth -- Theoderic's kingdom -- Theoderic's diplomacy -- Theoderic the lawgiver -- Amalasuintha and the legacy of Theoderic -- Part Four 540-70. Justinian I and the campaigns in North Africa and Italy. Belisarius captures Ravenna -- San Vitale, epitome of Early Christendom -- Narses and the Pragmatic Sanction -- Archbishop Maximian, bulwark of the West -- Archbishop Agnellus and the seizure of the Arian churches -- Part Five 568-643. King Alboin and the Lombard conquest. Alboin invades -- The exarchate of Ravenna -- Gregory the Great and the control of Ravenna -- Isaac, the Armenian exarch -- Agnellus the doctor -- Part Six 610-700. The expansion of Islam. The Arab conquests -- Constans II in Sicily -- The Sixth Oecumenical Council -- The Anonumous Cosmographer of Ravenna -- Part Seven 685-725. The two reigns of Justinian II. The Council in Trullo -- The heroic Archbishop Damianus -- The tempestuous life of Archbishop Felix -- Part Eight 700-769. Ravenna returns to the margins. Leo III and the defeat of the Arabs -- The beginnings of Iconoclasm -- Pope Zacharias and the Lombard conquest of Ravenna -- Archbishop Sergius takes control -- Part Nine 756-813. Charlemagne and Ravenna. The long rule of King Desiderius -- Charles in Italy, 774-87 -- Charles claims the stones of Ravenna -- Conclusion: The glittering legacy of Ravenna.
Online resource; title from digital title page (viewed on October 14, 2020).
Includes bibliographical references (pages 406-489) and index.
In English.
JSTOR
Keywords: Ravenna (Italy) -- History -- To 1500.; Ravenna (Italy) -- Church history; Cities and towns -- Italy -- History -- To 1500.; Ravenna (Italy) -- Kings and rulers -- Biography; Social history; Social Conditions; Histoire sociale; social history; HISTORY -- Medieval; Social history; Kings and rulers; Cities and towns; Italy; Italy -- Ravenna; To 1500; Arian Baptistry; Byzantine architecture; Church of San Vitale; City of Mosaics; Deborah Mauskopf Deliyannis; Eternal Ravenna; Europe's greatest cities; Exarchate of Revenna; From the Etruscans to the Venetians; Galla Placidia Mausoleum; Justinian mosaic; Jutta Dresken-Weiland.; Mariëtte Verhoeven; Massimiliano David; Ravenna in Late Antiquity; The Early Christian Monuments of Ravenna; great cities of Europe; medieval history; mosaics of Ravenna; mosaics of San Vitale; where in Italy should I visit?.; Church history; Biographies; History